2023
DOI: 10.1111/jpm.12901
|View full text |Cite
|
Sign up to set email alerts
|

Promoting and hindering factors in the use of advance statements by Australian mental health clinicians

Abstract: Accessible Summary What Is Known on the Subject? Australia is a commonwealth of federated states and territories with each having unique mental health legislation. Victoria implemented advance statements based on legislation from overseas jurisdictions such as Scotland. The aim of this Victorian legislation was to underpin an individual's autonomy and decision‐making in relation to treatment, particularly compulsory treatment. Advance statements allow individuals within the healthcare setting to document pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…All participants of this study reported using variations of these tools to provide ED clinicians with information to enable communication across services and assist with the continuity of person-centred care. It is unfortunate that these plans are at times overridden, yet it is hoped that barriers to implementation such as legal ramifcations [70], lack of training and access [71], and language used [70] among others, are addressed to promote consumer autonomy and a recovery focus [72].…”
Section: Connecting the Communication Silos-service Integrationmentioning
confidence: 99%
“…All participants of this study reported using variations of these tools to provide ED clinicians with information to enable communication across services and assist with the continuity of person-centred care. It is unfortunate that these plans are at times overridden, yet it is hoped that barriers to implementation such as legal ramifcations [70], lack of training and access [71], and language used [70] among others, are addressed to promote consumer autonomy and a recovery focus [72].…”
Section: Connecting the Communication Silos-service Integrationmentioning
confidence: 99%